Impact of varying germination periods on the nutritional quality and protein availability of four legumes - Devi, Reema; Sangwan, Veenu; Punia, Darshan (Bangladesh Journal of Botany, 2023)
To improve the quality and digestibility of legumes, and to examine effects of varying germination periods (6, 12 and 18 hrs) on the protein quantity, digestibility, ash, moisture, fibre and fat content of locally available legumes namely green gram, chickpea, lentil and moth bean the present study was undertaken. It was found that the protein content and protein digestibility of legumes increased by 4.87 to 42.79 and 3.48 to 19.77 per cent, respectively depending on the type of legume, and length of germination. The highest per cent increase in protein content was found in chickpea (42.79%) germinated for 18 hrs. Maximum increase in in-vitro protein digestibility (19.77 %) was noticed in moth bean, ranging from 5.31 to 19.77 per cent at 6, 12 and 18 hrs of germination. Highest enhancement in protein value was observed in legumes which were germinated for 18 hrs. In comparison to raw, a significant reduction was noted in the ash content of all types of germinated legumes and in terms of per cent, the decrease varied from 2.98 to 8.46. Moisture and crude fibre content increased significantly where fat content was decreased in all legumes. Processed legumes can serve as a functional food for augmenting the nutritional status of vulnerable sections of society. Bangladesh J. Bot. 52(3): 837-843, 20-23 (September)